An Integration of Emotional Intelligence and Peers on Strengthing Buddhist Character - Julia Surya; Puji Astuti, Diah Arum; Kabri (Journal of Education Reseach and Evaluation, 2024)
Bad characteristics, such as greed, arrogance, hatred, laziness, anxiety, and restlessness, must be eliminated. Therefore, it is necessary to strengthen the Buddhist Character by increasing emotional intelligence and having peers. Therefore, this study aims to analyze the influence of emotional intelligence and peers on strengthening Buddhist Character. This research uses quantitative methods with a causal associative research design. The population of this study was 342 students, and the sample used was 120 students. The data collection method is a questionnaire. The instrument in this research is a questionnaire sheet. The data analysis technique uses inferential statistical analysis. The data analysis results show a significant positive influence between emotional intelligence and strengthening Buddhist Character by 74.4%. Apart from that, there is a significant positive influence between peers on strengthening Buddhist Character by 62.8%. Apart from that, there is a significant positive influence between emotional intelligence and peers on strengthening Buddhist Character by 82.5%. It was concluded that the higher a person's emotional intelligence, the stronger their Buddhist Character. Apart from that, the better the quality of your peers, the higher your Buddhist Character will be strengthened. So, the higher the emotional intelligence and peer friends, the stronger the Buddhist Character will be. So, the higher the emotional intelligence and peer friends, the stronger the Buddhist character will be.